2018
DOI: 10.1002/cbic.201800135
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophile Promiscuity of Natural and Engineered Aldolases

Abstract: The asymmetric aldol addition reaction mediated by aldolases is recognized as a green and sustainable method for carbon-carbon bond formation. Research in this area has unveiled their unprecedented synthetic potential toward diverse, new chemical structures; novel product families; and even as a technology for industrial manufacturing processes. Despite these advances, aldolases have long been regarded as strictly selective catalysts, particularly for nucleophilic substrates, which limits their broad applicabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…The biocatalytic process in this study is elegant and nicely exploits the power of cascades: (i) it provides a universal, efficient, and renewable catalyst to replace precious transition metals such as Pd 10 , 11 in the modern chemical C–H functionalization-mediated asymmetric assembly of α-functionalized organic acids and (ii) when compared to other enzymatic methods 3 5 , 9 , 26 , 28 , 36 , 39 , the universality and practicality of this biocatalytic cascade is more attractive owing to the more diverse product range that it supports, including liphatic, aromatic, heteroaromatic, and heterocyclic products from three classes (α-keto/hydroxy/amino acids). Furthermore, since enantiocomplementary ʟ- and D -specific TAs were identified to accept nucleophilic substrates other than glycine (such as alanine, serine, and cysteine) 42 , 43 , the expansion of this biocatalytic process could enable the synthesis of a vast array of α-functionalized products simply by combinatorically integrating different components such as other catalyst modules and substrate units.…”
Section: Discussionmentioning
confidence: 99%
“…The biocatalytic process in this study is elegant and nicely exploits the power of cascades: (i) it provides a universal, efficient, and renewable catalyst to replace precious transition metals such as Pd 10 , 11 in the modern chemical C–H functionalization-mediated asymmetric assembly of α-functionalized organic acids and (ii) when compared to other enzymatic methods 3 5 , 9 , 26 , 28 , 36 , 39 , the universality and practicality of this biocatalytic cascade is more attractive owing to the more diverse product range that it supports, including liphatic, aromatic, heteroaromatic, and heterocyclic products from three classes (α-keto/hydroxy/amino acids). Furthermore, since enantiocomplementary ʟ- and D -specific TAs were identified to accept nucleophilic substrates other than glycine (such as alanine, serine, and cysteine) 42 , 43 , the expansion of this biocatalytic process could enable the synthesis of a vast array of α-functionalized products simply by combinatorically integrating different components such as other catalyst modules and substrate units.…”
Section: Discussionmentioning
confidence: 99%
“…A particular success in this area is fructose-6-phosphate aldolase (FSA), an aldolase that accepts dihydroxyacetone as donor but also other ketones and even some aldehydes (Garrabou et al 2009 ; Junker et al 2018 ). This donor or nucleophile promiscuity was recently reviewed (Hernandez et al 2018 ).
Scheme 2 Four groups of aldolases according to the functionality of their donor substrates, above the arrows (acetaldehyde, dihydroxyacetone (phosphate), pyruvate dependent or phosphoenolpyruvate, and glycine)
…”
Section: Introductionmentioning
confidence: 99%
“…The interesting feature is the substrate promiscuity as DERA enzymes have been shown to accept a wide range of aldehydes as acceptor molecules, thus offering a biocatalytic alternative for a (stereo)selective synthesis of C-C bonds. Substrate specificity on the donor substrate side is stricter but recent biodiversity screen has revealed that some DERAs also display nucleophile substrate promiscuity (Hernández et al 2018;Chambre et al 2019). Furthermore, DERA enzymes can carry out a tandem reaction with acetaldehyde as a sole substrate, leading to formation of a C6 product, 2,4,6-trideoxyhexose, which cyclises spontaneously and is removed from the reaction.…”
Section: Discussionmentioning
confidence: 99%